ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TEACHING EFFICACY CALON GURU - Ai Nur Solihat; Satya Santika (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to determine how much influence the preparation of learning programs, attitudes toward the teaching profession towards teaching efficacy of prospective teachers. The method used in this study is the explanatory survey method. The subjects in this study were level IV students of the Siliwangi University Teaching and Education Faculty (FKIP). The sampling technique used was proportionate random sampling (proportional random sample). The data analysis technique in this study is multiple linear regression using the SPSS 23.0 statistical tool to determine the effect of the preparation of learning programs, attitudes toward the teaching profession towards teaching efficacy of prospective teachers. Based on the results of the study, simultaneous preparation of learning programs and attitudes towards the teaching profession has a positive influence on teaching efficacy. That is, if there is an increase in the preparation of learning programs and attitudes towards the teaching profession simultaneously, it will improve the teaching efficacy of prospective teachers. Partially the preparation of learning programs has a significant effect on teaching efficacy of 0.271. That is, if there is an increase in the preparation of the learning program by 0.271 units then teaching efficacy will increase by 0.271 units, and attitudes towards the teaching profession have a significant influence on teaching efficacy of 0.459. This means that if there is an increase in attitudes towards the teaching profession by 0.459 then teaching efficacy increases by 0.459 units.Keywords: Factors Affecting Teachers' Teaching Efficacy